FINANCIAL MANAGEMENT PRACTICES AND PERFORMANCE OF MINISTRIES, DEPARTMENTS AND AGENCIES (MDAS) IN SOUTH WEST NIGERIA (Journal of Global Accounting, 2025)
This study examined the effect of financial management practices on performance of Ministries, Departments, and Agencies (MDAs) in South-west Nigeria. A two-stage sampling technique was used to select the participants. Primary data was obtained through the administration of questionnaire to 262 respondents out of the total population of 824, comprising employees of the Board of Internal Revenue, Accountant-General and Auditor General Office for the State, and the Ministry of Finance, Budget, and Planning across six South-west states. Data obtained was analyzed using descriptive statistics and Correlations, and Partial Least Squares-Structural Equation Model PLS-SEM. The results revealed that financial budgeting practices (t-stat=5.26, p-v
Keywords: Budgeting Practices; Financial Management Practices; MDAs; Performance